Measuring Islamic Boarding School Kiai's Legal Istinbat regarding Election Jurisprudence in Indonesia from the Perspective of Political Jurisprudence Principles - Shofiyulloh, Shofiyulloh; Ridwan, Ridwan; Rufaida, Arini (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Islamic boarding school kiai have a role in society as heirs of the Prophets. They are considered to have the capacity for religious understanding to provide the best solutions to the problems of the people, including those related to the general elections in 2024. This research aims to analyze the legal istinbat of Islamic boarding school kiai related to general elections in Indonesia from the perspective of political jurisprudence rules. The main issues studied in this research are the legal istinbat of Islamic boarding school Kiai regarding general election jurisprudence in Indonesia, the legal istinbat of Islamic boarding school kiai in responding to political issues in Indonesia, and the legal istinbat of Islamic boarding school kiai in formulating the rules of political jurisprudence in Indonesia. This research uses the method of istinbat usul fiqh law and fiqh rules. In applying the formulation of kiai thinking through the method of political jurisprudence, the concept of istiqra'i digital literature is used. This research concludes that the Islamic boarding school kiai's legal istinbat is based on a fiqh mindset which refers to the madhabi-manhaji. Meanwhile, political issues are interpreted by Islamic boarding school kiai as wasilah which refers to the noble goal of building a better Indonesia. Islamic boarding school kiai's thoughts about politics are often colored by the rules of political jurisprudence.